Γ-radiation, chemical synthesis of Ce3+: Gd2Si2O7/SiO2 nanocomposite. (December 2021) - Ladjouzi, S.; Guerbous, L.; Bensuici, F.; Bendiba, G.
Abstract: In this work, Ce 3+ :Gd2 Si2 O7 /SiO2 (0.1 mol% Ce 3+ ) nanocomposite powders were successfully synthesized via γ-irradiation, followed by thermal treatment at 900 °C for 2h.The radiations were carried out in a 60 Co γ-source chamber at a dose up to 50 kGy. The structural, morphological and optical properties were investigated using X-ray diffraction analysis (XRD), Raman spectroscopy, Transmission electron microscopy (TEM) and Photoluminescence (PL) spectroscopy. XRD analysis reveals the formation of pure orthorhombic δ-Gd2 Si2 O7 Gadolinium pyrosilicate (δ-GPS)crystalline phase. The average particles size ranges from 30 to 50 nm when the γ-doses increase up to 50 kGy. Raman scattering shows that the intensity of Raman bands significantly increases with increasing of γ-doses. TEM observations show well dispersed spherical GPS nanoparticles within the silica glass host and confirmed the particles size and size distribution dependence on the γ-irradiation dose. Finally, photoluminescence measurements show that the emission intensity corresponding to 5d-4f transition of Ce 3+ increases with increasing of γ-irradiation dose due to high purity, better crystallinity and uniform distribution of Ce 3+ ions into GPS nanostructures. Highlights: Ce 3+ :Gd2 Si2 O7 /SiO2 nanocomposite powders were prepared by γ-irradiation combined with the thermal treatment at 900 °C for 2h. γ-Ray irradiation(10–50 kGy) induced crystallization of Ce 3+ :Gd2 Si2 O7 nanoparticles. γ-Ray irradiation increases the crystallitesize from 30 to 50 nm. γ-Ray irradiation up to a dose of 50 kGy, improves the emission intensity of Ce 3+ : Gd2 Si2 O7 /SiO2 nanocomposite.